James Stirling's post-avant-garde collage: the flatbed picture plane & the pursuit of virtuality. Issue 3 (September 2021) - Proto, Francesco
Abstract : The second decade of the twenty-first century has been distinguished by a renewed interest in James Stirling and his architectural heritage – a sort of 'James Stirling Renaissance' – with many authors characterising Stirling predominantly as a late modernist architect.